Macrobenthic Assessment of the South Sandwich Islands Reveals a Biogeographically Distinct Polar Archipelago - Hogg, Oliver T.; Downie, Anna-Leena; Vieira, Rui P.; Darby, Chris (Frontiers in Marine Science, 2021)
The sub-Antarctic South Sandwich Islands forms part of one of the largest marine protected areas (MPAs) in the world. Whilst the neighbouring island of South Georgia is known to be a biodiversity hotspot, very little was known about the benthic biodiversity or biogeography of the South Sandwich Islands. Here we present findings from the first biophysical assessment of this polar archipelago. Using open-access datasets, alongside results from a recent UK Government-funder Blue Belt expedition to the region, we assess how the island’s biodiversity is structured spatially and taxonomically and how this is driven by environmental factors. The South Sandwich Islands are shown to be both biologically rich, and biogeographically distinct from their neighbouring provinces. A gradient forest approach was used to map the archipelago’s benthic habitats which, based on the functional composition of benthic fauna and environmental characterisation of the benthic environment, demonstrated a distinct biogeographical north-south divide. This faunal and environmental discontinuity between the South Sandwich Islands and the rest of the MPA and between the different islands of the archipelago itself, highlights the importance of the zoned protection across the South Georgia and South Sandwich Islands Marine Protected Area.